Evaluating User Disorientation: A Comparison of Hypertext and Continuous Zooming Interfaces - Silva-Fh, José Bezerra da; Páez, Linda B.; Marchionini, Gary (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1996)
Hypertext systems have reached ubiquity in the World Wide Web (WWW). One of the most common side effects of hypertext use is disorientation and this problem is exacerbated in the WWW environment. Powerful workstations allow software engineers to create innovative interfaces that improve user performance while minimizing such side effects. One such innovation is continuous zooming, an interface mechanism that provides alternative control to scrolling and jumping. A series of studies were conducted to investigate how a continuous zooming interface affected user text comprehension performance in general and user disorientation. Results suggest that zooming in text is at least as good as hypertext jumping for comprehension tasks and that users are satisfied with zooming even with minimal practice.